Characterization of plasma in RF jet interacting with water: Thomson scattering versus spectral line broadening. (1st March 2022) - Yatom, Shurik; Oldham, Trey; Thimsen, Elijah
Abstract: In this work we carry out a detailed characterization of an Ar radiofrequency plasma jet interacting with liquid. The focus of the paper is measurement of the electron density by examining the Stark broadening of hydrogen Balmer α line and Thomson scattering (TS). Supporting diagnostics are done to investigate the channel evolution and movement, and gas temperature. The comparison of the two approaches shows the caveats and the advantages that should gain attention in future applications. In particular, the plasma channel dynamics have a significant impact on the TS signal and may result in physical phenomena being missed due to channel dislocations. The conclusions of the work elucidate the pitfalls for interpreting the results of TS when the discharge is a dynamic filamentary plasma. This work establishes the temporal evolution of the plasma and the gas parameters in a plasma–liquid system employed for investigation of plasma-induced electrodeless electrochemistry.